2017
DOI: 10.1177/1524839917708795
|View full text |Cite
|
Sign up to set email alerts
|

Community Health Workers and Use of mHealth: Improving Identification of Pregnancy Complications and Access to Care in the Dominican Republic

Abstract: This article presents the feasibility and acceptability of using mobile health technology by community health workers (CHWs) in San Juan Province, Dominican Republic, to improve identification of pregnancy complications and access to care for pregnant women. Although most women in the Dominican Republic receive four antenatal care visits, poor women and adolescents in remote areas are more likely to have only one initial prenatal visit to verify the pregnancy. This community-based research began when community… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 21 publications
(25 reference statements)
0
25
0
1
Order By: Relevance
“…Primarily, these studies tend to have a small sample size. For example, Bonnell et al (2018) included 8 CHWs and 52 pregnant women in three locations in the San Juan province of the Dominican Republic, while Mangwi Ayiasi et al (2015) included 36 interviews with women seeking maternity care and 26 key informant interviews in Uganda in their study. Although these studies were able to explore the use of mHealth qualitatively, the sample size does not allow for an assessment of any potentially statistically significant quantitative measures or outcomes, or for the drawing of conclusions that are generalizable to more diverse populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Primarily, these studies tend to have a small sample size. For example, Bonnell et al (2018) included 8 CHWs and 52 pregnant women in three locations in the San Juan province of the Dominican Republic, while Mangwi Ayiasi et al (2015) included 36 interviews with women seeking maternity care and 26 key informant interviews in Uganda in their study. Although these studies were able to explore the use of mHealth qualitatively, the sample size does not allow for an assessment of any potentially statistically significant quantitative measures or outcomes, or for the drawing of conclusions that are generalizable to more diverse populations.…”
Section: Discussionmentioning
confidence: 99%
“…Braun et al (2013) found that the majority of programs utilizing mHealth technology use by CHWs addressed issues related to maternal, sexual, and reproductive health, with more than half of this group specifically focused on HIV/AIDS. The reoccurring themes in CHWs and mHealth research included a focus on maternal health among populations of women living in low-and middle-income countries and rural areas (Bonnell et al, 2018). Such research also detailed how CHWs are able to bridge the gap between formal health care and lowincome or harder to reach communities (Braun et al, 2013), improve the health knowledge of midwives (S. Lee, Chib, & Kim, 2011), and speed up access to health data (Little et al, 2013).…”
Section: Mhealth Chws and Maternal Healthmentioning
confidence: 99%
“…The included papers were published from 1987 to 2018, with more than half (n=13) published in 2017 (n=5) and 2018 (n=8). A total of eight [36][37][38][39][40][41][42][43] papers were published in the United Kingdom, followed by the United States (n=4) [44][45][46][47], Belgium (n=4) [48][49][50][51], Dominican Republic (n=1) [52], Netherlands (n=1) [53], and Guatemala (n=1) [54]. One study [55] described two different versions of a telemonitoring intervention being implemented in Nigeria, Mozambique, Pakistan, and India.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…All interventions collected maternal blood pressure, with some interventions collecting additional metrics such as heart rate; weight; activities; urinalysis for glucose and protein; symptoms of preeclampsia such as headache, epigastric pain, and visual symptoms; temperature; peripheral capillary oxygen saturation; and psychosocial signs and symptoms. In addition, four articles [51][52][53][54] collected data from the fetus, including fetal heart rate and kick count. A total of six unique studies [37,38,[41][42][43]45,46] reported interventions in which only maternal blood pressure was collected.…”
Section: Intervention Characteristicsmentioning
confidence: 99%
“…Several retrospective and prospective studies have recommended the use of home blood pressure monitoring (HBPM) in pregnancy because of its potential benefits including fewer hospital visits, better blood pressure control, and cost savings [12][13][14][15]. A scoping review conducted in 2019 found 16 unique TM interventions from 20 studies [12,14,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] for patients at high-risk for hypertensive disorders of pregnancy, but these studies have not translated to sustained programs [34]. The scoping review concluded that TM for hypertension during pregnancy was feasible, convenient, and cost-effective.…”
Section: Introductionmentioning
confidence: 99%